Raising the Bar: Improving Antimicrobial Resistance Detection by Clinical Laboratories by Ensuring Use of Current Breakpoints. (7th February 2022) - Simner, Patricia J; Rauch, Carol A; Martin, Isabella W; Sullivan, Kaede V; Rhoads, Daniel; Rolf, Robin; She, Rosemary; Souers, Rhona J; Wojewoda, Christina; Humphries, Romney M
Abstract: Background: Antimicrobial resistance (AMR) is a pressing global challenge detected by antimicrobial susceptibility testing (AST) performed by clinical laboratories. AST results are interpreted using clinical breakpoints, which are updated to enable accurate detection of new and emerging AMR. Laboratories that do not apply up-to-date breakpoints impede global efforts to address the AMR crisis, but the extent of this practice is poorly understood. Methods: A total of 1490 clinical laboratories participating in a College of American Pathologists proficiency testing survey for bacterial cultures were queried to determine use of obsolete breakpoints. Results: Between 37.9% and 70.5% of US laboratories reported using obsolete breakpoints for the antimicrobials that were queried. In contrast, only 17.7%–43.7% of international laboratories reported using obsolete breakpoints ( P < .001 for all comparisons). Use of current breakpoints varied by AST system, with more laboratories reporting use of current breakpoints in the US if the system had achieved US Food and Drug Administration clearance with current breakpoints. Among laboratories that indicated use of obsolete breakpoints, 55.9% had no plans to update to current standards. The most common reason cited was manufacturer-related issues (51.3%) and lack of internal resources to perform analytical validation studies to make the update (23.4%). Thirteen percent of laboratories indicated they were unaware of breakpoint changes or the need to update breakpoints. Conclusions: These data demonstrate a significant gap in the ability to detect AMR in the US, and to a lesser extent internationally. Improved application of current breakpoints by clinical laboratories will require combined action from regulatory agencies, laboratory accreditation groups, and device manufacturers.